Agribisnis Terpadu Bersistem Leisa di Lahan Basah : Model Hipotetik - Mugnisjah, Wahju Q.; Suwarto, ,; Solihin, Ahmad S. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
LEISA refers to forms of agriculture that seek to optimize the use of locally available resources by combining the different components of the farm system (i.e. plants, animals, soil, water, climate and people) so that they complement each other and have the greatest possible synergetic effects: In the system of LEISA proposed here, ecological risks generated by the external inputs are avoided; and reversally, the farm system performance is enriched by the use of internal inputs (including by products)p reduced in the agro-ecosystem. The external inputs in the form of agro-chemicals (inorganic fertilizers and pesticides) are used in a limited to replace nutrients transported out of the agro-ecosystem through harvest. Selecting a hypothetical model of LEISA by integrating crop production (1.25 ha),fish nursery (0.50 ha), and duck husbandry (1000 ducks at the dike of pond) shows that the system being feasible. The hypothetical model needs investation cost as much as Rp 64 195 000 and operational cost of Rp 41289825, giving a total cost of Rp 105484825 (as lending cost). Based on the estimation of monthly cash flow with annual DF 18% and grace period of 11 months, the hypothetical model gives NPV at the 36th month = Rp 38 556 960, Net B/C = 1.43, IRR = 39.42. and payback periods = 25 months. Key words: Leisa, Agribisniss, Wet land, Model